THE PREVALENCE OF GLUCOSE-6-PHOSPHATE DEHYDROGENASE (G6PD) DEFICIENCY IN HEALTHY BLOOD DONORS IN KARACHI, PAKISTAN: A MALARIA ENDEMIC AREA - Moiz, Bushra; Brohi, Sana (Infectious Diseases Journal of Pakistan, 2022)
Background: Annually 3.5 million presumed and confirmed significant cases of malaria are reported in Pakistan. The hypnozoite stage of Plasmodium vivax can be eradicated via antimalarial i.e. Primaquine, and this drug causes hemolysis in G6PD enzyme deficient individuals. Therefore, it is important to map malaria distribution and G6PD deficiency in malaria endemic area i.e., Karachi Pakistan to design an effective malaria eradication regimen. Material and Methods: Adult healthy male blood donors, were recruited after informed consent during 1st March 2018 till 30th November 2020 in a hospital blood bank at Karachi, Southern Pakistan. G6PD enzyme was measured by a qualitative method (Trinity Biotech Glucose-6-Phosphate Dehydrogenase Qualitative Kit catalogue no. 400-10*10, Sweden) based on detecting the rate of reduction of NADP to NADPH through decolourization of dye. Tested individuals were classified as G6PD-normal, -intermediately deficient, and –completely deficient based on color change within the time frame of 20, 20-60 and after 60 minutes. Results: 29 (8.4%) out of 342 adult male blood donors were identified to be G6PD deficient. 28 (8.1%) were intermediately deficient for G6PD deficiency while one was completely deficient (0.3%). Conclusion: Our small-scale study indicated an appreciable frequency of G6PD deficiency in Karachi Pakistan, requiring mandatory G6PD screening prior to administration of primaquine for malaria eradication. Large-scale studies are required for complete mapping of the city which will eventually build into malaria-roll-out program. Keywords: Deficiencies, Glucose phosphate dehydrogenase, G6PD deficiency, Blood donors, Anemia, Hemolysis, Malaria